2017
DOI: 10.12973/ejac.2017.00293a
|View full text |Cite
|
Sign up to set email alerts
|

Preconcentration of Gadolinium Ion by Solidification of Floating Organic Drop Microextraction and Its Determination by UV-Vis Spectrophotometry

Abstract: A solidified floating organic drop microextraction (SFODME) combined with UV-Vis spectrophotometry was applied for preconcentration and determination of Gd(III). In this study, Morin (3, 5, 7. 2', 4' pentahydroxy flavone) as a suitable ligand and 1-Dodecanol as extraction solvent were used. Following the extraction Gd-Morin complex, the extraction solvent was transported to a spectrophotometer for determination of Gadolinium ion at the absorption wave length of 440 nm. The main affecting factors in the perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…When the organic solvent is solidified, by using a spatula the extraction solution is collected in a test tube, and the melted organic solvent is used for the determination of analyte [20]. Due to its efficient merits, SFODME is a simple, quick, and low‐cost technique where the extraction is done up to a small volume (µL) of an extractant at a melting point near room temperature (10–30°C) [19, 21, 22]. A systematic procedure has been illustrated in Figure 4.…”
Section: The General Procedures Of Sfodmementioning
confidence: 99%
See 3 more Smart Citations
“…When the organic solvent is solidified, by using a spatula the extraction solution is collected in a test tube, and the melted organic solvent is used for the determination of analyte [20]. Due to its efficient merits, SFODME is a simple, quick, and low‐cost technique where the extraction is done up to a small volume (µL) of an extractant at a melting point near room temperature (10–30°C) [19, 21, 22]. A systematic procedure has been illustrated in Figure 4.…”
Section: The General Procedures Of Sfodmementioning
confidence: 99%
“…According to the convective‐diffusive mass transfer theory, stirring is a crucial parameter in extraction methods for improving the extraction dynamics [35]. The rate of stirring has a direct impact on droplet characteristics and mass transfer, in the SFODME method very high stirring rate can generate splatter and decrease the required time to achieve the equilibrium between the droplet and the sample solution [21]. The aqueous‐phase mass‐transfer coefficient increases with increasing the stirring rate, various studies showed that the effective stirring rate for various metal ions is in the range of 300–1200 rpm [21, 32, 34, 36].…”
Section: Factors Affecting the Performance Of Sfodmementioning
confidence: 99%
See 2 more Smart Citations